Prospecção de marcadores microssatélites, análise de viriabilidade e estrutura genética populacional de arara-azul-grande Anodorhynchus hyacinthinus (Latham, 1790) com ênfase na região do mosaico dos Carajás-PA - Silva, Helder Elias da [UNESP] (2014)
Hyacinth macaw (Anodorhynchus hyacinthinus), the largest parrot in the world, is considered vulnerable to extinction (IUCN) mainly due to habitat loss and illegal trade. To establish strategies for the conservation of the species must be regarded the genetic makeup of their populations. Commonly for the study of genetic diversity and population genetic structure are used molecular markers, highlighting specially the microsatellite loci, which in turn need to be isolated for population studies. However, currently there is no polymorphic microsatellite loci identified in A. hyacinthinus. Additionally, the species is distributed in three apparently isolated areas, thus requiring integrated management in order to preserve the gene pool of the species. Thus, the main objectives of this study were: (i) the development of primers for microsatellite loci in Anodorhyncus hyacinthinus, and (ii) the analysis of the diversity and population genetic structure of all areas of occurrence of the species. Six loci species-specific prospected were obtained (AnH6, AnH10, AnH17, AnH23, AnH33 and AnH34) and five of these primers proved to be polymorphic. In addition, these six pairs of primers showed potential applicability for population studies after they were tested in seven Neotropical parrot species. Regarding the population analyzes using both specific and heterologous loci, A. hyacinthinus presented a low level of genetic variability compared to other parrots, thereby indicating that the low variability found should not be related to the use of only heterologous loci in previous studies, suggesting that this is an intrinsic characteristic of this species. Moreover, considering in the analysis of genetic structure by Bayesian clustering of microsatellite data it could not be found genetic structure between subpopulations of four regions [North Pantanal (NP), South Pantanal (SP), Para (PA) and northeast (NE)]. In contrast, Rst indices indicated ...